Does migration affect education of girls and young women in Tajikistan? - Kseniia Gatskova; Artjoms Ivlevs; Barbara Dietz (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
We study how migration affects education of girls in Tajikistan - the poorest post-Soviet state and one of the most remittance-dependent economies in the world. Using data from a three-wave household panel survey conducted in 2007, 2009, and 2011, we find that the effect of migration on girls' school attendance differs markedly by age. School attendance of young girls (ages 7-11) improves when either parents or sibling migrate, as well as when the household starts receiving remittances. In contrast, school attendance of teenage girls (ages 12-17) falls when siblings migrate, while parental migration and remittances have no effect. Having a grandmother as the head of household after parents (typically fathers) migrate improves school attendance of young and teenage girls, but reduces school attendance of young women (ages 18-22). We also find that in localities where the share of migrants is already high, an increase in the share of migrant households is associated with an increase in the marriage rate. Our results support various channels through which emigration of household members may affect girls' and young women's education: relaxation of budget constraints, increase in household work, change in the head of household, and pressure to marry early. Overall, our study suggests that the net effect of migration on girls' schooling turns from positive to negative with girls' age; this implies that migration may be detrimental to women's empowerment in Tajikistan and casts doubts on whether migration is an appropriate long-term development strategy for this country.
Keywords: F22; F24; I21; J16; J24; 330; female empowerment; girls' education; migration; remittances; Tajikistan